Odpowiedzi

2010-01-14T18:24:50+01:00
A)
3x+y=5
2x-y=0
+---------
5x=0
x=0
y=5
b)
2x-y=5
x+y=4
+----------
3x=9
x=3
6-y=0
x=3
y=6
c)
-x-y=-6
-x+y=2
--------------
-2x=-4
x=2
y=-4
d)4x-5y=-4
-2x+3y=1,1/2
4x-5y=-4
-4x+6y=2,2
+--------------
y=-1,8
4x-9=-4
y=1,8
x=0,8

e) -2x+y=0/3
3x-3y=1
-6x+3y=0
3x-3y=1
+---------
-3x=1
x=-1/3
y=0
f) 3x-2y=-12/2
2x-5y=-19 /(-3)
6x-4y=-24
-6x+15y=57
+------------
11y=33
y=3
x=3i 1/3
Najlepsza Odpowiedź!
2010-01-14T18:34:56+01:00
A)3x+y=5
2x-y=0
(skreślamy y)
5x=5/5
x=1
3*(razy)1+y=5
x=1
3+y=5
x=1
y=5-3
x=1
y=2

b) 2x-y=5
x+y=4
(skreślamy y)
3x=9/3
x=3
3+y=4
x=3
y=4-3
x=3
y=1

c) -x-y=-6
-x+y=2
(skreślamy y)
-2x=-4/2
x=2
-2-y=-6
x=2
-y=-6+2
x=2
-y=-4/(-1)
x=2
y=4

d) 4x-5y=-4 (tu chyba jest jakaś pomyłka)
-2y+3y=1,1

f) 3x-2y=-12 I razy 5
2x-5y=-19 I razy (-2)
15x -10y=-60
-4x+10y=38
(skreślamy y)
11x=-22/11
x=-2
3 razy -2-2y=-12
x=-2
-6-2y=-12
x=-2
2y=-12+6
2y=-6/2
x=-2
y=-3